2019
DOI: 10.1017/s0021932018000421
|View full text |Cite
|
Sign up to set email alerts
|

Did family size affect differences in body height in non-urbanized societies? Evidence from the Lemko community in Poland in the late 19th and early 20th centuries

Abstract: The aim of this study was to examine the effect of economic changes in the Polish territories under Austrian partition at the end of the 19th and the beginning of the 20th centuries on the trend in adult body height, and to examine the effect of number of children in a family, as a socioeconomic factor, on the differences in heights of males and females. Data collected in a 1939 survey for a group of 350 Lemkos living in Polish lands under the Austrian partition were obtained from archive material. Individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 43 publications
(56 reference statements)
1
2
0
Order By: Relevance
“…The results were consistent with a previous analysis which showed that young adult heights of Polish women born during the war were about 2 cm shorter and attained menarche later than those born before and after the WWII (Liczbińska et al 2017(Liczbińska et al , 2019. This study, however, focused on dates of birth and did not take into consideration the potential influence of pregnancies that spanned only part of the war.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The results were consistent with a previous analysis which showed that young adult heights of Polish women born during the war were about 2 cm shorter and attained menarche later than those born before and after the WWII (Liczbińska et al 2017(Liczbińska et al , 2019. This study, however, focused on dates of birth and did not take into consideration the potential influence of pregnancies that spanned only part of the war.…”
Section: Discussionsupporting
confidence: 90%
“…Unfortunately, information on birth weight was not available for the women in the present analysis. Earlier analyses (Liczbińska et al 2017(Liczbińska et al , 2019 have shown that heights of young adult women born before, during and after WWII were related to father's level of education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation